Investigating Attitudes toward Those Who Leave Religion among Christian, Jewish, and Muslim Believers - Eylem Kanol; Ines Michalowski (Religions, 2022)
This study investigates the determinants of negative attitudes toward individuals who leave their religion, i.e., converts and apostates, among Christian, Jewish, and Muslim believers. Drawing on the literature from the study of religion and prejudice, we identify and test the explanatory power of three dimensions of religiosity: religious practice, religious fundamentalism, and religious knowledge, while an alternative hypothesis focuses on the role of education. Our data is derived from a cross-sectional survey fielded among more than 8000 Christian, Jewish, or Muslim respondents in 7 countries. Using ordinary least squares regression analyses, we find that, across the three religious groups, both religious practice and religious fundamentalism are strongly associated with negative feelings toward converts and apostates. Although the effect of religious knowledge is negligible, educational attainment significantly predicts lower levels of unfavorable attitudes. We conclude by discussing some notable differences between the three religious groups and between the countries in which these groups and individuals are located.
Additional information: Open-access publication of this article was funded by the Open Access Fund of the Leibniz Association and WZB Berlin Social Science Center.
Keywords: 300; apostates; converts; attitudes; fundamentalism; religious knowledge; Islam; Christianity; Judaism